Is Ophrys pollination more opportunistic than previously thought? Insights from different field methods of pollinator observation. Issue 3 (3rd July 2021) - Schatz, Bertrand; Genoud, David; Escudié, Pascal; Geniez, Philippe; Wünsch, Karl Günter; Joffard, Nina
ABSTRACT: Global changes induce a general decline in the abundance and diversity of European orchids and their pollinators. Such a decline is especially likely to affect species engaged in specialized interactions, thereby causing their replacement by generalists. In this study, we focused on sexually deceptive orchids from the genus Ophrys, which are often described as extreme specialists. We describe several observations of Ophrys pollinators in the Mediterranean region in order to: i) compare four different field methods to monitor Ophrys pollinators, and ii) provide more information on these pollinators to re-evaluate the specialization of Ophrys -pollinator interactions and discuss the ecological context in which these interactions take place. We discovered several new pollinator species for various Ophrys taxa, including unexpected ones. We also showed that the prolonged observation of mass-flowering and neighbouring Ophrys plants optimizes the chances of observing Ophrys pollinators without disturbing natural pollination. We argue that Ophrys pollination may be more opportunistic than classically described in the literature, likely involving one main pollinator and one or several secondary pollinators across the range of each Ophrys species. This study provides new methodological and conceptual insights into Ophrys pollination.